The Working Memory as Predictor of Performance in Arithmetic of Brazilian Students. - David Vieira, Fernanda; Oliveira Ribeiro, Denise; Blesa Farias, Heitor; Martins Freitas, Patricia (Paideia (0103863X), 2021)
Working memory (WM) is a predictor of school learning. This study aimed to investigate the predictive power of verbal and non-verbal working memory (WM) on students' performance in arithmetic. 126 children between 6 and 11 years old participated in the research. The instruments were: School Performance Test, Raven's Colored Progressive Matrices, Corsi Block-tapping Test, and Digits Subtest. The results showed strong and positive correlations of school performance with fluid intelligence r = 0.64, with verbal WM and non-verbal WM, both with r = 0.51 (p < 0.001). After multiple linear regression, it was found that the performance in visuospatial WM was a strong predictor for arithmetic, an effect not found for reading. The regression showed that WM explains 38% of the variance for arithmetic. It is concluded that WM has an expressive contribution to school performance, being more specific the contributions of visuospatial WM for arithmetic.